Revisión endoscópica ante el fallo de la Tercer Ventriculostomía en pacientes pediátricos - Grisotto , L; Colombo, G; Tello Brogiolo , N; Bustamante, J; D´Agustini, MO (Revista Argentina de Neurocirugía, 2021)
Introduction:Endoscopic third ventriculostomy (TVE) is currently considered the method of choice for the treatment of hydrocephalus regardless of etiology, with a success rate between 50-80%. However, treatment when it fails is widely discussed. Endoscopic revision (Re-TVE) allows evaluating the characteristics of the stoma and, if necessary, re-waterproofing it, avoiding the use of ventricular shunt systems. The objective of this study is to describe the intraoperative findings and analyze the efficacy of Re-TVE as a treatment for hydrocephalus in the same center. Materials and methods: We performed a retrospective study from January 1, 2014, to December 31, 2020 (6 years), in patients with a diagnosis of hydrocephalus treated with TVE, in which the endoscopic review was performed at the time of the failure. Sex, age, etiology of hydrocephalus, signs and symptoms at the time of clinical presentation, time elapsed since the first procedure and the failure, the therapeutic strategy implemented, the intra-surgical findings, the complications and the results were analyzed. Results: Thirteen patients were included, 11 were under 2 years of age. The average interval between the first TVE and the review was 186 days. Regarding the origin of hydrocephalus, 4 (30%) were secondary to myelomeningocele, 4 (30%) to intraventricular hemorrhage, 3 (23%) to CNS infections and 2 (15%) to congenital pathologies. The procedure was successful in 4 (30%) patients, all under 2 years of age. As an intraoperative finding, the ostomy was classified as: complete closure, closure of the ostomy due to arachnoiditis, and patent ostomy. There were no complications in any case. The average follow-up period is 26 months. Conclusion: Re-TVE represents a safe technique, which can be considered as a therapeutic option in the event of TVE failure. The selection of the patient must be careful, being essential to establish clear criteria that allow to improve the success rate.